Flavonoids from the Leaves of Citrus aurantium (Sour Orange) and Citrus sinensis (Sweet Orange) - Haggag, E.G.; Mahmoud, I.I.; Abou-Moustafa, E.A.; Mabry, T.J. (Asian Journal of Chemistry, 2010)
Polymethoxylated flavonoids and flavonoid O- and C-glycosides were isolated and identified from extracts of the leaves of Citrus aurantium var. amara L (sour orange) and Citrus sinensis L (sweet orange). Altogether twenty-three flavonoids were obtained from the two species (Table-1). This is the first report of four of the polymethoxylated flavonoids from leaves of C. sinenis, namely tetra-O-methyl scutallrein, queratagetin, hexamethyl ether, isosinensetin, and sinensetin; the latter two were also obtained for the first time from the leaves of C. aurantium. This is also the first report of several C-glyosides of apigenin and diosmetin from the two species (see Table-1). Furthermore, this is the first report of neodiosmin, poncirin, narirutin glucoside and naringin glucoside from the leaves of C. aurantium.